Multiparametric magnetic resonance imaging and frozen-section analysis efficiently predict upgrading, upstaging, and extraprostatic extension in patients undergoing nerve-sparing robotic-assisted radical prostatectomy. Issue 40 (October 2016) - Bianchi, Roberto; Cozzi, Gabriele; Petralia, Giuseppe; Alessi, Sarah; Renne, Giuseppe; Bottero, Danilo; Brescia, Antonio; Cioffi, Antonio; Cordima, Giovanni; Ferro, Matteo; Matei, Deliu Victor; Mazzoleni, Federica; et al.
Abstract : Abstract: To evaluate the role of multiparametric magnetic resonance imaging (mpMRI) in predicting upgrading, upstaging, and extraprostatic extension in patients with low-risk prostate cancer (PCa). MpMRI may reduce positive surgical margins (PSM) and improve nerve-sparing during robotic-assisted radical prostatectomy (RARP) for localized prostate cancer PCa. This was a retrospective, monocentric, observational study. We retrieved the records of patients undergoing RARP from January 2012 to December 2013 at our Institution. Inclusion criteria were: PSA <10 ng/mL; clinical stage <T3a; biopsy Gleason score <7; prostate mpMRI performed preoperatively at our Institution; intraoperative FSA of the posterolateral aspects of the specimen. All the identified lesions were scored according to the Prostate Imaging Reporting and Data System (PIRADS). We considered the lesion with the highest PIRADS score as index lesion. All the included patients underwent nerve-sparing RARP. During surgery, the specimen was sent for FSA of the posterolateral aspects. The surgeon, according to the localization scheme provided by the mpMRI, inked the region of the posterolateral aspect of the prostate that had to be submitted to FSA. We evaluated association between clinical features and PSM, upgrading, upstaging, and presence of unfavorable disease. Two hundred fifty-four patients who underwent nerve-sparing RARP were included. PSM rate was 29.13% and 15.75% at FSA and final pathology respectively. Interestingly, the use of FSA reduced PSM rate in pT3 disease (25.81%). Higher PIRADS scores demonstrated to be related to high probability of upgrading and upstaging. This significativity remains even when considering PIRADS 2–3 versus 4 versus 5 and PIRADS 2–3 versus 4–5. Also PSM at FSA were associated with higher probability of upgrading and upstaging. PIRADS score and FSA resulted to be strictly related to grading and staging, thus being able to predict upgrading and/or upstaging at final pathology.